Cost-effectiveness of a complex continuum of care intervention targeting women and children: protocol for an economic evaluation of the Bukhali trial in South Africa - Norris, Shane A.; Palmer, Tom; Granados, Rolando Leiva; Draper, Catherine; Batura, Neha (BMJ Publishing Group, 2024)
Introduction: As nearly two-thirds of women presenting at their first antenatal visit are either overweight or obese in urban South Africa, the preconception period is an opportunity to optimise health and offset transgenerational risk of both obesity and non-communicable diseases. This protocol describes the planned economic evaluation of an individually randomised controlled trial of a complex continuum of care intervention targeting women and children in Soweto, South Africa (Bukhali trial). Methods and analysis: The economic evaluation of the Bukhali trial will be conducted as a within-trial analysis from both provider and societal perspectives. Incremental costs and health outcomes of the continuum of care intervention will be compared with standard care. The economic impact on implementing agencies (programme costs), healthcare providers, participants and their households will be estimated. Incremental cost-effectiveness ratios (ICERs) will be calculated in terms of cost per case of child adiposity at age years averted. Additionally, ICERs will also be reported in terms of cost per quality-adjusted life year gained. If Bukhali demonstrates effectiveness, we will employ a decision analytical model to examine the cost-effectiveness of the intervention over a child’s lifetime. A Markov model will be used to estimate long-term health benefits, healthcare costs and cost-effectiveness. Probabilistic sensitivity analyses will be conducted to explore uncertainty and ensure robust results. An analysis will be conducted to assess the equity impact of the intervention, by comparing intervention impact within quintiles of socioeconomic status. Ethics and dissemination: The Bukhali trial economic evaluation has ethical approval from the Human Ethics Research Committee of the University of the Witwatersrand, Johannesburg, South Africa (M240162). The results of the economic evaluation will be disseminated in a peer-reviewed journal and presented at a relevant international conference.
Keywords: Overweight; Obese; Health providers; Health care cost; South Africa; SDG-3: Good health and well-being